Cardiometabolic Risk Factors in Men with Elevated Macroprolactin Content: A Pilot Study - Krysiak, Robert; Szkróbka, Witold; Okopień, Bogusław (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Macroprolactinemia is a condition associated with the presence of large amounts of high molecular weight complexes of prolactin. Despite high prevalence, clinical significance of macroprolactin remains poorly understood.Objective The aim of this study was to assess cardiometabolic risk in men with isolated macroprolactinemia.Methods The study population included 11 men with isolated macroprolactinemia, 14 subjects with monomeric hyperprolactinemia and 14 men with prolactin levels within the reference range. Glucose homeostasis markers, plasma lipids, as well as plasma levels of uric acid, high-sensitivity C-reactive protein (hsCRP), fibrinogen, homocysteine and 25-hydroxyvitamin D were determined in all included patients.Results Compared to healthy counterparts, men with isolated macroprolactinemia had higher levels of 2-h postchallenge glucose, hsCRP and fibrinogen, lower levels of 25-hydroxyvitamin D and reduced insulin sensitivity. Patients with monomeric hyperprolactinemia were characterized by increased plasma levels of 2-h postchallenge glucose, triglycerides, uric acid, hsCRP, fibrinogen and homocysteine, reduced insulin sensitivity and decreased plasma concentrations of HDL cholesterol and 25-hydroxyvitamin D. Subjects with isolated macroprolactinemia differed from patients with monomeric hyperprolactinemia in postchallenge plasma glucose, insulin sensitivity, uric acid, hsCRP, fibrinogen, homocysteine and 25-hydroxyvitamin D. In men with monomeric hyperprolactinemia, uric acid, hsCRP, fibrinogen, homocysteine and 25-hydroxyvitamin D, while in men with elevated levels of macroprolactin, uric acid, hsCRP, fibrinogen and 25-hydroxyvitamin D correlated with a content of monomeric prolactin or macroprolactin, respectively, as well as with a degree of insulin sensitivity.Conclusions The obtained results suggest that macroprolactinemia may increase cardiometabolic risk but to a lesser extent than monomeric hyperprolactinemia.
Keywords: cardiovascular risk; macroprolactin; monomeric prolactin; risk factors